PENGARUH PEMBELAJARAN SISTEM KOLOID DENGAN MENGGUNAKAN MACROMEDIA FLASH TERHADAP HASIL BELAJAR DAN RETENSI HASIL BELAJAR SISWA KELAS XI IPA SMA NEGERI 1 TAPA (Suatu Penelitian di Kelas XI IPA SMA Negeri 1Tapa TP 2008/2009) - Salila, Musrin; Pikoli, Masrid; Suleman, Nita (Jurnal Entropi, 2009)
Colloid system [is] a[n mixture form which its [of] located nya [among/between] suspense and condensation ( harsh mixture). Name of colloid given by Thomas Graham in the year 1861. That term Come from yunani Ianguage, that is \" Kolla\" and \" Oid\". Kolla Mean glue while Oid like. In this case related to glue [is] the nature of its diffusion, because colloid system have low dipusi value like glue because its bigger fairish particle than molecule, that is maximum 1 micrometer. Flash Macromedia [is] animation object creator application which [is] powerful. Added with making [of] graphical object [of] vektor which consist in in it, pemprograman [of] Actionscript. such Animassi that is from atom particle motion and molecule which [do] not look with indra pentameter, generalizing cannot from perception, have to earn generalizing with theory. Result learn [is] ability [of] student in knowledge aspect, understanding of, application, analysis, sintesis, and evaluation [at] colloid system items where this ability [is] obtained to [pass/through] media study [of] flash macromedia. ability [of] Student in the aspect expressed in tes score result of learning. Retention result of learning [is] ability [of] student remember items which have been taught by teacher [at] spanning certain time. Retention result of learning student [is] in this case expressed in retention tes score result of learning. This research aim to Know result learn for the items of taught colloid system by using higher flash macromedia from [at] which [is] taught without using flash macromedia and to know retention result of learning for the items of taught colloid system by using higher flash macromedia from [at] which [is] taught without using flash macromedia. This research represent research [of] eksperimental with used [by] pelitian device [at] this research [is] post test design group controle only with XI IPA SMA Country I class student population Live as an ascetic school year 2008 / 2009. Research Sampel divided two class with the each experiment class by using flash macromedia and class control without using flash macromedia with amount of [is] same student that is 21 people. used instrument in the form of objeksif tes. Before tes used to net data, beforehand analyze indicator of[is quality of tes that is executed [by] reliabilitas and validity [in] SMA Country 4 Gorontalo. Validity Tes obtained 100% and reliabilitas equal to 0,69. Result of research obtained a) [at] tes test result of learning experiment class by using higher obtained score flash macromedia that is = 76,87 compared to tes dennga result of learning [at] class control without using flash macromedia with obtained score = 68,54 in hypothesis test concluded that in signifikan level 0,01 with dk = 40 in the reality diperolen assess thitung = 3,93 > from ttabel ( 0,995)(20) = 2,84 and H0 [in] refusing so that can be expressed that result learn natural student [of] study by using flash macromedia by signifikan compared to better [of] natural student [of] study without using macromedia b) [at] retention tes test result of learning experiment class by using higher obtained score flash macromedia that is = - 29,08 compared to tes dennga result of learning [at] class control without using flash macromedia with obtained score = - 30,10 in hypothesis test concluded that in signifikan level 0,01 with dk = 40 in the reality diperolen assess thitung = 0,34 < from ttabel ( 0,995)(20) = 2,84 and H0 [in] accepting so that can be expressed that result learn natural student [of] study by using flash macromedia by signifikan compared to better [of] natural student [of] study without using macromedia from hopotesis test [at] retention tes result of learning to be categorized [by] there [is] [relation/link] in study by using flash macromedia.